2017
DOI: 10.1080/00015458.2017.1353236
|View full text |Cite
|
Sign up to set email alerts
|

In- and out-hospital mortality rate in surgical patients

Abstract: In-hospital mortality alone is an incomplete measure of mortality even within 30 days of care. To identify the missing deaths, hospital records need to be linked to data from death certificate. This connection with the national death registry will allow obtaining the rate of in-hospital and out-hospital death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…A 2018 study that evaluated in-and out-of-hospital deaths involving adult patients who were admitted for elective and nonelective inpatient surgery reported that out-of-hospital deaths after inpatient surgery accounted for 18% of 30-day mortality. 15 Other studies have shown how the proportions of out-of-hospital deaths were dependent on the type of surgery, with out-of-hospital deaths ranging from 8% (bladder) to 50% (breast) after cancer surgeries, 16 and 53% after hip fracture surgeries. 5 We found lower proportions of out-of-hospital deaths compared with the literature.…”
Section: Discussionmentioning
confidence: 98%
“…A 2018 study that evaluated in-and out-of-hospital deaths involving adult patients who were admitted for elective and nonelective inpatient surgery reported that out-of-hospital deaths after inpatient surgery accounted for 18% of 30-day mortality. 15 Other studies have shown how the proportions of out-of-hospital deaths were dependent on the type of surgery, with out-of-hospital deaths ranging from 8% (bladder) to 50% (breast) after cancer surgeries, 16 and 53% after hip fracture surgeries. 5 We found lower proportions of out-of-hospital deaths compared with the literature.…”
Section: Discussionmentioning
confidence: 98%
“…This number of postoperative deaths accounts for 7.7% of all deaths globally, making it the third greatest contributor to deaths in the world [ 1 ]. In a study of the University Hospital of Charleroi in Belgium, post-operative mortality rates within 30 post-operative days were 1.1% [ 2 ]. In this hospital, risk factors of post-operative mortality were identified as the absence of an anesthesia nurse, American Society of Anesthesiologists scores (ASA scores) > 2, emergency, duration of surgery and rate of admission to critical care unit [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Nearly half of all adverse events (AEs) in hospitalized patients are related to surgical care and at least half of the cases in which surgery led to harm are considered preventable. 3 There has been an increasing focus on and advancement in improving the safety culture in the operating room (OR) in order to prevent AEs. The OR may be particularly vulnerable to sentinel events which can result in death, permanent or severe temporary harm.…”
Section: Introductionmentioning
confidence: 99%